Wykorzystanie internetu w zarządzaniu działaniami marketingowymi w przedsiębiorstwie - Kałążna-Drewińska, Urszula (The use of internet in management of marketing operations in an enterprise, 2006)
The purpose of the article is to demonstrate the possibilities of Internet use as a source of useful knowledge or even indispensable knowledge in management of marketing operations in enterprises. The article consists of following parts: introduction, the methods of marketing information gathering in a company, the examples of using of computer and Internet in management of marketing operations in a company, conclusion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 221-232